Stakeholder assessment of weed management practices and perceptions of targeted spraying technologies in corn-soybean systems - Ugljic, Zaim; Mobli, Ahmadreza; Oliveira, Maxwel Coura; Proctor, Christopher A.; Dille, J. Anita; Werle, Rodrigo (Frontiers in Agronomy, 2025)
IntroductionUnderstanding regional weed control practices and stakeholder perspectives is essential to guide the development and adoption of novel weed management technologies. This survey aimed to evaluate chemical weed control practices, major weed escapes, and stakeholder perceptions of targeted spraying technologies in corn and soybean cropping systems across the U.S. Midwest.MethodsA survey was conducted from fall 2021 to spring 2022 in corn (Zea mays L.) and soybean [Glycine max (L.) Merr.] cropping systems across the Western U.S. Midwest Region (WUMR: Kansas and Nebraska) and the Eastern U.S. Midwest Region (EUMR: Illinois, Minnesota, and Wisconsin). It assessed currently adopted herbicide programs, end-of-season weed escapes, and awareness of targeted spraying technologies among growers, advisors, and applicators.ResultsSurvey responses (128 participants) indicated that over 50% of growers used a two-pass herbicide application program [preemergence (PRE) followed by postemergence (POST) with layered residual] in soybean and corn across both regions in 2021. The top weed escapes in WUMR corn fields were Palmer amaranth (Amaranthus palmeri S.Wats.), waterhemp [Amaranthus tuberculatus (Moq.) J.D.Sauer], and foxtail species (Setaria spp.), while for soybean fields, Palmer amaranth, waterhemp, and volunteer corn were most common. Conversely, EUMR respondents primarily reported foxtail spp., waterhemp, and giant ragweed (Ambrosia trifida L.) escapes in corn and waterhemp, giant ragweed, and volunteer corn in soybean fields. Over 49% of respondents believe that novel targeted spraying technologies could help control late season weed escapes. However, more than 75% are unsure whether these technologies will be adopted in the operations they manage in the future, with 48% indicating the need of more information to support their decision. The survey results showed a greater reliance on commercial applicator services in the EUMR than WUMR, highlighting the potential role of commercial applicators in advancing effective herbicide strategies and targeted spraying technologies adoption while reducing the need for farmers to invest in new equipment within the EUMR region.DiscussionThis survey highlights substantial opportunities for targeted herbicide application technologies research and outreach education involving regulatory agencies, spray manufacturers, chemical companies, decision influencers, University Extension and other parties.